Comparative Study of Integrated Quality Management Practices in SMEs in the Manufacturing Sector and Service Sector on Company Performance - Anggita Rafiah Khoerunnisa; Titik Kusmantini; Yekti Utami (Jurnal Inovasi Bisnis dan Kewirausahaan, 2022)
This study aims to identify a series of TQM practices followed in the SME Handicraft manufacturing sector and in the Tour & Travel SME service sector in Bantul. In collecting data this research used a questionnaire. The distribution of the questionnaires was carried out by distributing directly to 30 craftsmen of the handicraft center SMEs and 30 of the Tour and Travel Service Industry SMEs in Bantul, Yogyakarta. The analytical method used is comparative can be solved using the average difference test. The results show that there are differences in the priority of TQM dimensions in manufacturing and service SMEs. Total Quality Management has a significant positive effect on company performance in manufacturing SMEs. Total Quality Management has a significant positive effect on Company Performance in SME services